DVB‐T based passive radar for simultaneous counter‐drone operations and civil air traffic surveillance. Issue 4 (1st April 2020) - Martelli, Tatiana; Colone, Fabiola; Cardinali, Roberta
Abstract : The effectiveness of DVB‐T based passive radar (PR) in counter drones operations is investigated in this study aiming at monitoring airport terminal areas. In particular, the authors demonstrate that such sensors could be effectively employed to provide simultaneous short‐range surveillance against drones and long‐range monitoring of aircraft from civil air traffic. To this purpose, several experimental tests have been performed with the DVB‐T based AULOS® passive sensor developed by Leonardo S.p.A. using very small RCS drones as cooperative targets along with conventional air traffic as targets of opportunity. An appropriate signal processing architecture is proposed for the two search tasks to be accomplished simultaneously. This is extensively applied against the collected datasets, based on the algorithmic solutions devised by the research group at Sapienza University. The reported results clearly prove the capability of a DVB‐T based PR of simultaneously detecting and localising drones flying around the airport area as well as the typical civil aircraft at longer distances.